Conversion of CO2 and small alkanes to platform chemicals over Mo2C-based catalysts. (14th April 2021) - Marquart, Wijnand; Claeys, Michael; Fischer, Nico
Abstract : Evaluating the effect of synthesis technique and metal oxide support material on the catalytic performance of Mo2 C in the CO2 assisted oxidative dehydrogenation of C2 H6 . Abstract : The performance of Mo2 C-based catalysts in CO2 assisted oxidative dehydrogenation (CO2 -ODH) of ethane was evaluated. Mo2 C on SiO2 was synthesized via three different techniques: wet impregnation (WI), hybrid nanocrystal technique (HNC) and sol–gel method (SG) and exposed to the same carburization conditions. In terms of characteristic properties, the allotrope composition was the most affected, with the SG sample containing MoO x C y and the WI and HNC samples containing β-Mo2 C. The two different allotropes were suggested to follow different reaction pathways, leading to small differences in the catalytic performance. However, overall, all three catalysts showed a decrease in activity (below 6%) and an increase in C2 H4 selectivity (from 60 to 80 C%) with time on stream (TOS). The deactivation mechanism was suggested to be mainly due to oxidation of the carbide to MoO x and carbon deposition. Mo2 C was also supported on various metal oxide materials via the wet impregnation technique. Mo2 C supported on Al2 O3 and ZrO2 increased initial activity (about 8% C2 H6 conversion) but a faster deactivation with TOS was observed. Mo2 C/Ga2 O3 favoured the direct dehydrogenation reaction achieving high C2 H4 selectivities (above 80 C%), but deactivation with TOS due to carbon deposition was significant. Mo2 C supported on CeO2 and TiO2 had lower activity (about 3% C2 H6 conversion). Oxidation to MoO2 and carbon deposition is again suggested to be the main deactivation mechanism. H2 co-feeding, on Mo2 C/SiO2 and Mo2 C/ZrO2, increased the stability of the catalysts but C2 H4 yield was affected (from 5 to 2%). At 17 vol% H2 co-feeding, Mo2 C/ZrO2 showed promising catalyst stability over a 20 h period, paralleled by a stable C2 H4 yield.